EFFECTS OF GENISTEIN EXPOSURE TOWARD INITIAL DEVELOPMENT OF CENTRAL NERVOUS SYSTEM IN CHICKEN EMBRYO MODEL (GALLUS GALLUS) AGE 48 HOURS - Rahayu, Indriati Dwi; Paundralingga, Obed Trinurcahyo Kinantyo; Sari, Vidia Purnama (Malang Neurology Journal, 2018)
Background. The safety of genistein consumption in the first trimester of pregnancy and its effect on embryonic development, especially in the development of Central Nervous System (CNS) is still not widely known.Objective. To determine the effect of genistein exposure to the early development of the Central Nervous System.Methods. The animal model used in this research is chick embryo (Gallus gallus). Genistein at a dose of 5 µM, 10 µM and 20 µM in ovo injected into the yolk sac of the eggs before incubation. The eggs were then incubated for 48 hours at a temperature of from 37.50 to 38.50 C. After 48 hours, broken egg shell, embryos are taken and carried out using Toluidine Blue staining. The evaluation was done on the neural tube, anterior neuropore, posterior neuropore and somites.Results. It was found neural tube defects in the group treated with genistein more than the control group but the result was not statistically significant.Conclusion. For the somites, in the group treated with a dose of 10 µM genistein, the number of somites more than the control group and statistically the number is significant.